Pelatihan Kewirausahaan dengan Membuat Lukisan untuk Membangun Jiwa Kreatif dan Inovatif Siswa Kelas VIII C di MTs 4 Sinjai - Suriyati; Jaya Nur, Makmur; Judrah, Muh; Agustina; Hanif, Fikri (IKHLAS: Jurnal Pengabdian Dosen dan Mahasiswa, 2024)
The aim of this training is to provide basic knowledge and skills about entrepreneurship and encourage students to think creatively and innovatively in designing business ideas. The focus is to provide entrepreneurship training with a focus on painting to class VIII C students at MTs 4 Sinjai, with the aim of developing a creative and innovative spirit in a business context. The research method used is a project-based learning approach, which allows active and collaborative involvement of 23 students in the learning process. The training process includes several stages, from identifying needs and planning to implementation, monitoring and evaluation. The initial stage of training involves identifying students' needs and their potential through surveys, interviews, and discussions. After that, training planning is carried out which includes determining content, schedule and clear objectives. The results show an increase in students' understanding of entrepreneurship, painting skills, and appreciation of the economic potential of their artwork. Thus, this training succeeded in achieving its goal of developing students' creative and innovative souls for a better future. In conclusion, entrepreneurship training by making paintings makes a positive contribution to developing students' skills and preparing them to face future challenges